Global Domestic Workers Intersectional Inequalities and Struggles for Rights - Cherubini, Daniela (Bristol University Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC licence. Drawing from the EU-funded DomEQUAL research project across 9 countries in Europe, South America and Asia, this comparative study explores the conditions of domestic workers around the world and the campaigns they are conducting to improve their labour rights. The book showcases how domestic workers' movements put 'intersectionality in action' in representing the interest of various marginalized social groups from migrants and low-income groups to racialized and rural girls and women. Casting light on issues such as subjectification, and collective organizing on the part of a category of workers conventionally regarded as unorganizable, this ambitious volume will be invaluable for scholars, policy makers and activists alike.EPDF and EPUB available Open Access under CC-BY-NC licence. Drawing from the EU-funded DomEQUAL research project across 9 countries in Europe, South America and Asia, this comparative study explores the conditions of domestic workers around the world and the campaigns they are conducting to improve their labour rights. The book showcases how domestic workers' movements put 'intersectionality in action' in representing the interest of various marginalized social groups from migrants and low-income groups to racialized and rural girls and women. Casting light on issues such as subjectification, and collective organizing on the part of a category of workers conventionally regarded as unorganizable, this ambitious volume will be invaluable for scholars, policy makers and activists alike.